Whistling past the graveyard : amnesty and the right to an effective remedy under the African Charter : the case of South Africa and Mocambique - Matusse, Angelo (University of Pretoria, 2006)
Thesis (LLM (Human Rights and Democratisation in Africa)) -- University of Pretoria, 2004.